2004
DOI: 10.1598/rrq.39.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gap: Addressing the vocabulary needs of English‐language learners in bilingual and mainstream classrooms

Abstract: S Gaps in reading performance between Anglo and Latino children are associated with gaps in vocabulary knowledge. An intervention was designed to enhance fifth graders' academic vocabulary. The meanings of academically useful words were taught together with strategies for using information from context, from morphology, from knowledge about multiple meanings, and from cognates to infer word meaning. Among the principles underlying the intervention were that new words should be encountered in meaningful text, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
254
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(281 citation statements)
references
References 15 publications
16
254
0
4
Order By: Relevance
“…The empirical basis for the distinction between depth and breadth comes primarily from experimental studies in which instructional approaches targeting ''deep'' word knowledge have been found to be effective in promoting reading comprehension (e.g., Beck, Perfetti, & McKeown, 1982;Carlo et al, 2004;Lesaux, Kieffer, Faller, & Kelley, 2010;Silverman, 2007). Multiple reviews and meta-analyses (e.g., National Institute of Child Heath and Human Development (NICHD), 2000; Stahl & Fairbanks, 1986) concur that instruction that provides rich information about words' meanings and uses in multiple, varied contexts is preferable to instruction that aims to increase the number of words for which students know a single definition, if the ultimate goal is enhancing reading comprehension.…”
Section: Breadth and Depth Of Vocabulary Knowledgementioning
confidence: 99%
“…The empirical basis for the distinction between depth and breadth comes primarily from experimental studies in which instructional approaches targeting ''deep'' word knowledge have been found to be effective in promoting reading comprehension (e.g., Beck, Perfetti, & McKeown, 1982;Carlo et al, 2004;Lesaux, Kieffer, Faller, & Kelley, 2010;Silverman, 2007). Multiple reviews and meta-analyses (e.g., National Institute of Child Heath and Human Development (NICHD), 2000; Stahl & Fairbanks, 1986) concur that instruction that provides rich information about words' meanings and uses in multiple, varied contexts is preferable to instruction that aims to increase the number of words for which students know a single definition, if the ultimate goal is enhancing reading comprehension.…”
Section: Breadth and Depth Of Vocabulary Knowledgementioning
confidence: 99%
“…In the last fifty years researchers examined how dual language, or bilingual practices, support students learning English versus how immersion programs work (Carlo et al, 2004;Cheung & Slavin, 2005;Han, 2012;Rolstad, Mahoney, & Glass, 2005). Other researchers investigated the length of time it takes for ELL students to become fully proficient in the mainstream classroom, suggesting that full academic language proficiency may take up to seven years for students (Barr, Eslami, & Joshi, 2011;Coleman & Goldenberg, 2010;Hakuta, Butler, & Witt, 2000).…”
Section: Pedagogical Practices For English Language Learnersmentioning
confidence: 99%
“…In a recent study of vocabulary depth, adolescents in fifth grade were explicitly taught individual words and word learning strategies, including the use of context, polysemy, and Spanish-English cognates (all semantically based strategies) to learn word meanings (Carlo et al, 2004). Students in the intervention group outperformed their control group counterparts in pre-post vocabulary and comprehension growth.…”
Section: Semantic Depth Instruction and Interventionmentioning
confidence: 99%
“…Nagy and Herman (1985) showed that incidental exposure to words through reading was a major source of vocabulary acquisition. Interventions that strive to incorporate specific target words throughout a variety of textual Bilingual and monolingual vocabulary 521 experiences can manipulate the degree to which words are encountered through independent reading (Carlo et al, 2004). Incorporating these varied yet important perspectives into a single intervention requires deliberate planning to include a broader array of learners than is traditionally considered in most instructional designs.…”
Section: Vocabulary Instructional Design and Deliverymentioning
confidence: 99%
See 1 more Smart Citation